Remote Instrumentation and Virtual Laboratories Service Architecture and Networking - Davoli, Franco; Meyer, Norbert; Pugliese, Roberto; Zappatore, Sandro; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Remote Instrumentation and Virtual Laboratories focuses on all aspects related to the effective exploitation of remote instrumentation; on making instrumentation fully integrated into the e-Science scenario by considering middleware, networking, and metrological aspects; and the building of complex virtual laboratories on top of real devices and infrastructures. These include SOA and related middleware, high-speed networking in support of Grid applications, wireless Grids for acquisition devices and sensor networks, Quality of Service (QoS) provisioning for real-time control, measurement instrumentation and methodology, as well as metrology issues in distributed systems. The activities generally termed "e-Science" encompass a wide range of scientific disciplines. It is characterized by highly intensive computation on huge data sets in a large-scale distributed environment, by the real-time interaction and collaboration among many scientists working on a specific problem or data set worldwide, and by the use of specific instrumentation—the pieces of equipment physically producing the data that pertain to a certain experiment. In addition to remote instrumentation, this book also addresses new challenges that will arise from wireless access, wireless sensor networks, and the traversal of heterogeneous network domains.
Remote Instrumentation Services -- Open Grid Forum Research Group: Remote Instrumentation Services in Grid Environment – Overview of Activities -- Adapting the Instrument Element to Support a Remote Instrumentation Infrastructure -- Performance Analysis of a Grid-Based Instrumentation Device Farm -- Experimental Characterization of Wireless and Wired Access in Distributed Laboratories -- Virtual Laboratory and Its Application in Genomics -- Grid Infrastructure, Services and Applications -- The European Grid Initiative (EGI) -- Virtual Appliances: A Way to Provide Automatic Service Deployment -- Job Scheduling in Hierarchical Desktop Grids -- Towards QoS Provision for Virtualized Resources in Grids -- From Grid Islands to a World Wide Grid -- The Anatomy of Grid Resource Management -- SZTAKI Desktop Grid: Adapting Clusters for Desktop Grids -- SoRTGrid: A Grid Framework Compliant with Soft Real-Time Requirements -- A Data Grid Architecture for Real-Time Electron Microscopy Applications -- A Network-Aware Grid for Efficient Parallel Monte Carlo Simulation of Coagulation Phenomena -- Interactivity Management -- Practical Mechanisms for Managing Parallel and Interactive Jobs on Grid Environments -- Int.eu.grid -- Interactivity in Grid Computing in the Presence of Web Services -- Fusion Simulations, Data Visualization Results and Future Requirements for the Interactive Grid Infrastructure -- Interactive Grid-Access Using MATLAB -- Collaborative Interactivity in Parallel HPC Applications -- Interactive and Real-Time Applications on the EGEE Grid Infrastructure -- Supporting Services -- g-Eclipse – A Middleware-Independent Framework for Accessing Existing Grid Infrastructures -- Semantics-Based Context-Aware Dynamic Service Composition -- Distributed e-Science Application for Computational Speech Science -- SynchroNet -- Discovery of Resources in a Distributed Grid Environment Based on Specific Service Level Agreements (SLAs) -- Inter-Domain SLA Enforcement in QoS-Enabled Networks -- eVLBI and Cosmic Rays Detection -- High-Bandwidth Data Acquisition and Network Streaming in VLBI -- Real-Time Software Correlation -- AugerAccess – Virtual Infrastructure for Simulating Complex Networks -- Metrology Issues -- Challenges and Design Issues in a Distributed Measurement Scenario -- The Distributed Measurement Systems: A New Challenge for the Metrologists -- Recent Progresses of the Remote Didactic Laboratory LA.DI.RE “G. Savastano” Project -- A Software Architecture for the m-Learning in Instrumentation and Measurement -- Sensor Networks for Measurement -- Performance of Linear Field Reconstruction Techniques with Noise and Correlated Field Spectrum -- Hybrid Zigbee–RFID Networks for Energy Saving and Lifetime Maximization -- A Service-Oriented Wireless Sensor Network for Power Metering -- Performance Evaluation of a Robust Data Aggregation Approach in Diverse Sensor Networking Environments.
Keywords: Electrical engineering; Computer communication systems; Signal processing; Image processing; Speech processing systems; Electronics; Microelectronics; Communications Engineering, Networks; Computer Communication Networks; Signal, Image and Speech Processing; Electronics and Microelectronics, Instrumentation